Reversal Rate of Clustering of Cardiovascular Disease Risk Factors of Metabolic Syndrome in the General Population: The Niigata Preventive Medicine Study - Shinsuke Okada; Akiko Suzuki; Hiroshi Watanabe; Toru Watanabe; Yoshifusa Aizawa (Journal of Obesity)
The reversal rate from clustering of cardiovascular disease (CVD) risk factors—components of the metabolic syndrome (MetS) is not known. Methods and Results. Among 35,534 subjects who received the annual health examinations at the NiigataHealth Foundation (Niigata, Japan), 4,911 subjects had clustering of 3 or more of the following CVD risk factors: (1) body mass index (BMI) ≥25 Kg/m2, (2) blood pressure ≥130 mm Hg in systolic and/or ≥85 mm Hg in diastolic, (3) triglycerides ≥150 mg/dL, (4) high-density lipoprotein cholesterol ≤40 mg/dL in men, ≤50 mg/dL in women, and (5) fasting blood glucose ≥100 mg/dL. After 5 years 1,929 subjects had a reversal of clustering (39.4%). A reversal occurred more often in males. The subjects with a reversal of clustering had milder level of each risk factor and a smaller number of risk factors, while BMI was associated with the least chance of a reversal. Conclusion. We concluded that a reversal of clustering CVD risk factors is possible in 4/10 subjects over a 5-year period by habitual or medical interventions. Gender and each CVD risk factor affected the reversal rate adversely, and BMI was associated with the least chance of a reversal.